I Like Living Here. Social Stratas Attachment to the Hungarian Big Cities - Judit Berkes (DETUROPE)
Territorial identity and attachment have raised the awareness of researchers from the beginning, as social processes exert a powerful impact on the functioning and also the competitiveness of territories in certain cases. The investigation of these processes is crucial, while citizens, the local population are able to shape and influence the development path of an area. In the perspective of the analysis, social disparities can be defined on one hand from a horizontal and on the other, a vertical or spatial aspect. For the purposes of the current paper, the author used a population survey database of TÁMOP-4.2.2.A-11/1/KONV-2012-0069 project entitled „Social conflicts – social well-being and security, competitiveness and social development”. The investigation of the social structure of the full sample in light of aggregate economic principal components and two aggregate principal components of trust was followed by the analysis of the spatially distinct microsocial structures.